Spacecraft formation flying responsive mission optimum Delta-V and ground performance measures - Yahya, Nor Affendy (2022)
The slow turnaround time issue dwindling with a new planned space mission which is to cater for a rapid Earth’s surface observation demand had stimulated the growing interest in the concept of responsive space mission. Weighing on all the factors that involved, initiating a brand new dedicated single spacecraft mission proved to be rather time-consuming and not cost-effective, especially when the acquisition of an instantaneous critical land information is prioritized for. Therefore, the best solution to this problem is to slew the existing distributed space platform to the desired land area of interest. In this research, a case study was conducted by manipulating the satellite formations that are operating in orbit to fulfill the demands for the responsive space. The selection of the spacecraft formation flying mechanism meant to address the stated problem was due to its better performances delivered, simple structures, high reliability and longer operating lifetime compared to any other approaches available in the field. Both findings on the orbit and ground segment analyses derived from the formation flying application will be presented with the main objective is to acquire the optimum results for solving the problems. Particularly for an orbital analysis subject, each stage of the flight to be examined along with its corresponding configuration until the formation established on the final responsive orbit to determine the right amount of fuel needed. This case study employed three different modes of finite-thrust impulse namely, the one-impulse transfer, the two-impulse transfer, and the three-impulse transfer maneuver to find the required local minimum and the global minimum delta-V during the formation orbital transfer phase. As for the ground segment analysis, formation performances were measured based on four implicit variables, namely the formation ground area of coverage, the overlap coverage area, the formation ground swath length, and the formation relative geodesic. Cross-studies of these inter-dependent parameters were conducted at varying formation distances, altitudes, as well as inclinations, to acquire some specific trends so as to determine the optimum configuration for the excellent formation ground metric performance. Case study results revealed the practicality of employing satellite formation flying to address the needs for a responsive space mission both in terms of the orbital fuel preference and the ground metric requirement. The novel graphing techniques exploiting the plots of some dependent variables enables the decision to be made faster. Furthermore, the proposed technique has the advantage of providing multiple potential solutions instead of a single solution that is acquired through the conventional approach of solving the derived analytical approximated formulation. For an orbital transfer phase, the solutions to the problem of fuel optimization constituting different types of finite impulse transfers can be found from the selected graphs, which contain some distinct signature features. In the event where the leaderfollower formation is established, the higher amount of consumed retrograde fuel is necessary to retain the longitudinal separation between them as the formation separates farther. Several other factors that contribute to this delta-V variation include the total transfer time until target site arrival, the operating initial orbit semi-major axis, and the number of orbit revolution made. While the formation reconfiguration stage is equally critical, the fuel amount needed is found to be directly proportional to the increment in the formation distances. In addition to these factors, the formation ground assessment revealed that by positioning the formation at the right altitude within the low Earth orbit region while orbiting the Earth at high polar orbit inclination angle at near distance formation will produce the criterion of optimal desired ground performance. The criterion is the large acquisition of land coverage area, which has longer and wider ground coverage swath while possessing the least possible relative geodesic anomaly. Further investigation found that the occurrence of geodesic lengthening and shortening phenomenon were mainly influenced by the factor of sub-satellite point at high latitude positioning and the right azimuthal angle. Consequently, the presence of inconsistent relative geodesic attributes has significantly altered the overall computation accuracies of the ground area of coverage and its swath length properties.